Effects of Chemical Fertilization and Microbial Inoculum on Bacillus subtilis Colonization in Soybean and Maize Plants - Bueno, Clara Barros; dos Santos, Roberta Mendes; de Souza Buzo, Fernando; de Andrade da Silva, Maura Santos Reis; Rigobelo, Everlon Cid (Frontiers in Microbiology, 2022)
Plant growth-promoting endophytic microorganisms in agriculture has been expanding in Brazil and is an excellent strategy to face the challenges of current agriculture, such as reducing production costs with fewer environmental impacts, without detriment to productivity. However, little is known about the factors that can affect the colonization of endophytic such as inoculant concentration and mineral fertilization. The present study aimed to evaluate the influence of these factors on soybean and maize crops and found that for soybean crops, the highest B. subtilis concentration of 1 x 104 and1 x 1010 CFU mL-1 promoted the highest number of recovered bacteria, when there was no mineral fertilization. However, mineral fertilization limited the number of recovered bacteria, suggesting that mineral fertilization interferes with endophytic colonization. For maize crops, the highest number of recovered bacteria occurred from the concentration of 1 x 106 CFU mL-1, not differing from the highest concentrations. A mineral fertilization dose of 25% promoted the greatest B. subtilis recovery compared to the other treatments. Regarding plant development, the highest microbial inoculum concentrations did not necessarily promote greater positive growth promotion effects compared to the concentration of 1 x 104 CFU mL-1 for both crops. The results also suggest that the higher number of endophytic bacteria recovered in the plant does not necessarily affect plant growth in the same proportion. For soybean plants, there is a strong tendency that with the increase in the B. subtilis inoculant concentration, the need for mineral fertilization doses to achieve the same plant development is consequently increased, and inoculations with 1 x 105 and 1 x 106 CFU mL-1 with fertilization doses between 44 and 62% are the ideal combinations for greater plant development. In maize plants, the best growth promotion response (height) was obtained using inoculation concentration of 1 x 102 and 1 x 1010 CFU mL-1, increasing according to the increase in fertilization doses. The findings suggest, for soybean crop, that these high inoculum concentrations required more photosynthetic metabolites from the plants and more nutrients from the soil. Thus, the need for mineral fertilization for plant growth must be increased.